Monitoring and management of vectors of citrus tristeza virus in Coorg mandarin - Pillai, K Gopalakrishana (The Indian Journal of Agricultural Sciences, 2008)
The aphid vectors of citrus tristeza virus were monitored in Coorg mandarin (Citrus reticulata B1anco)during 2004-06 in Coorg district of Karnataka. The aphid population on the plants peaked during June-July and was negatively correlated with maximum temperature. Peak catches of alate aphids were during December-January and negatively correlating with relative humidity and rainfall. Three neonicotinoids, viz. thiamethoxam (0.05%), imidacloprid (0.005%) and acetamiprid (0.005%) were the most effective chemicals for the control of vectors in the high rainfall region. Botanical formulations were not effective to control the post application reco1onization of aphids. Predators (Cheilomenes sexmaculata Fab.) reduced the aphid population significantly at 7 days after the release but not 2 months later.